Hybrid and participatory impact assessment in social ventures: rethinking social venture evaluation - Güngördü-Arıoğlu, Merve; Tuncalp, Deniz (Emerald, 2025)
Purpose This paper aims to explore and analyze effective methods for measuring the impact of social ventures. By examining existing frameworks such as Social Return on Investment (SROI) and Impact Reporting and Investment Standards (IRIS) and through qualitative case studies of Turkish social ventures, the study aims to identify the limitations and adaptability of these methodologies. The goal is to provide actionable recommendations for social entrepreneurs, policymakers, and stakeholders to enhance the accuracy and relevance of impact assessments, thereby contributing to the sustainability and effectiveness of social ventures. Design/methodology/approach This research employs a qualitative methodology, focusing on in-depth case studies of Turkish social ventures. Data collection involves a combination of direct interviews with social entrepreneurs, analysis of organizational reports, and review of relevant literature. The study examines existing impact assessment frameworks, such as Social Return on Investment (SROI) and Impact Reporting and Investment Standards (IRIS), assessing their applicability and limitations within the Turkish context. The research aims to identify context-specific challenges and innovative practices by analysing these case studies, offering insights into more effective and tailored impact assessment methodologies for social ventures. Findings The study reveals that while global impact assessment frameworks like Social Return on Investment (SROI) and Impact Reporting and Investment Standards (IRIS) are helpful, they often require adaptation to fit Turkey’s unique socioeconomic conditions. Key findings highlight the need for context-specific, resource-efficient, and participatory impact assessment tools. The case studies illustrate innovative practices in Turkey, such as integrating local cultural factors and leveraging technology for data collection. These insights underscore the importance of developing tailored methodologies that accurately capture social ventures' diverse impacts on varied regional contexts. Research limitations/implications The research is limited by its focus on a few case studies, which may not fully represent the diversity of social ventures across Turkey. Additionally, the reliance on qualitative data may introduce subjective biases. The dynamic nature of social issues and the evolving socioeconomic landscape in Turkey further complicate the development of standardized assessment tools. Despite these limitations, the study offers valuable insights into context-specific challenges and innovative practices, highlighting the need for adaptable and responsive impact assessment methodologies. Future research should expand the scope of case studies and explore quantitative approaches to complement the qualitative findings. Practical implications This study provides practical recommendations for social entrepreneurs, policymakers, and stakeholders to improve impact assessment practices in Turkey. It offers strategies to tailor global frameworks like SROI and IRIS to local conditions by emphasizing the need for context-specific, resource-efficient, and participatory tools. Social ventures can adopt these insights to enhance the accuracy and relevance of their impact assessments, ultimately improving their effectiveness and sustainability. Policymakers can use these findings to create supportive environments and policies that foster social entrepreneurship. At the same time, investors can better evaluate the social return on their investments by aligning their portfolios with their social objectives. Social implications The study underscores the importance of accurate and context-specific impact assessment in enhancing the effectiveness of social ventures in Turkey. By providing tailored methodologies, social ventures can better address local socioeconomic challenges, leading to more meaningful and sustainable social change. Improved impact assessment practices enable ventures to demonstrate their value more convincingly, attracting better stakeholder support from investors, policymakers, and the community. This can lead to increased funding, better policy support, and more robust community engagement, ultimately fostering a more vibrant and impactful social entrepreneurship ecosystem that drives positive societal transformation. Originality/value This paper offers original insights into the challenges and opportunities of measuring the impact of social ventures in Turkey, a context that has received limited attention in the existing literature. By analyzing these case studies, the research highlights innovative, context-specific practices that can be adapted to other regions with similar socioeconomic dynamics. The studys value lies in its practical recommendations for developing resource-efficient and participatory impact assessment tools that address the unique needs of social ventures. These findings contribute to the broader discourse on social impact assessment and offer valuable guidance for social entrepreneurs, policymakers, and investors.